Biochemical and Functional Analysis of Cyanobacterium Geitlerinema sp. LPS on Human Monocytes. (4th July 2019) - Swanson-Mungerson, Michelle; Williams, Philip G; Gurr, Joshua R; Incrocci, Ryan; Subramaniam, Vijay; Radowska, Kinga; Hall, Mary L; Mayer, Alejandro M S
Abstract: Cyanobacterial blooms are an increasing source of environmental toxins that affect both human and animals. After ingestion of cyanobacteria, such as Geitlerinema sp., toxins and lipopolysaccharide (LPS) from this organism induce fever, gastrointestinal illness, and even death. However, little is known regarding the effects of cyanobacterial LPS on human monocytes after exposure to LPS upon ingestion. Based on our previous data using Geitlerinema sp. LPS (which was previously named Oscillatoria sp., a genus belonging to the same order as Geitlerinema ), we hypothesized that Geitlerinema sp. LPS would activate human monocytes to proliferate, phagocytose particles, and produce cytokines that are critical for promoting proinflammatory responses in the gut. Our data demonstrate that Geitlerinema sp. LPS induced monocyte proliferation and TNF-α, IL-1, and IL-6 production at high concentrations. In contrast, Geitlerinema sp. LPS is equally capable of inducing monocyte-mediated phagocytosis of FITC-latex beads when compared with Escherichia coli LPS, which was used as a positive control for our experiments. In order to understand the mechanism responsible for the difference in efficacy between Geitlerinema sp. LPS and E. coli LPS, we performed biochemical analysis and identified that Geitlerinema sp. LPS was composed of significantly different sugars and fatty acid side chains in comparison to E. coli LPS. The lipid A portion of Geitlerinema sp. LPS contained longer fatty acid side chains, such as C15:0, C16:0, and C18:0, instead of C12:0 found in E. coli LPS which may explain the decreased efficacy and toxicity of Geitlerinema sp. LPS in comparison to E. coli LPS.